2002
DOI: 10.1017/s0025315402006203
|View full text |Cite
|
Sign up to set email alerts
|

Spectral sensitivities of five marine decapod crustaceans and a review of spectral sensitivity variation in relation to habitat

Abstract: The spectral sensitivities of five species of decapod crustaceans have been determined by electroretinogram measurements. Their spectral sensitivities conform to the general picture for marine crustacea with high sensitivity to blue-green wavelengths and some showing sensitivity to violet/near ultraviolet. Two deep-water species (Paromola cuvieri and Chaceon (Geryon) affinis) have spectral sensitivity maxima below 500 nm, whereas the three coastal species examined (Crangonallmani, Pandalus montagui and Nephrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 22 publications
1
37
0
3
Order By: Relevance
“…Although they are limited in their ability to identify the actual visual pigments, they give us direct information on how the eye reacts to a particular wavelength (that can either coincide with a visual pigment absorption maximum or be modified by any optical filtering). Considering this difference in techniques, along with good evidence that a two-visual-pigment system is somewhat common in decapod crustaceans (Johnson et al, 2002), we doubt that the Uca visual system contains only the single photoreceptor type measured in this study. Other evidence for a multiple-receptor system is provided by the selective chromatic adaptation experiments done by both Hyatt (Hyatt, 1975) and Horch et al (Horch et al, 2002), both providing results consistent with the existence of a putative short wavelength visual pigment.…”
Section: Visual Pigmentsmentioning
confidence: 63%
“…Although they are limited in their ability to identify the actual visual pigments, they give us direct information on how the eye reacts to a particular wavelength (that can either coincide with a visual pigment absorption maximum or be modified by any optical filtering). Considering this difference in techniques, along with good evidence that a two-visual-pigment system is somewhat common in decapod crustaceans (Johnson et al, 2002), we doubt that the Uca visual system contains only the single photoreceptor type measured in this study. Other evidence for a multiple-receptor system is provided by the selective chromatic adaptation experiments done by both Hyatt (Hyatt, 1975) and Horch et al (Horch et al, 2002), both providing results consistent with the existence of a putative short wavelength visual pigment.…”
Section: Visual Pigmentsmentioning
confidence: 63%
“…In addition, it is of paramount importance in designing experiments in aquaria to consider the light environment carefully. Light is a key determinant of behaviour of mesopelagic organisms and they tend to be specifically adapted to cope with a particular light intensity, in addition to defined spectral, spatial and temporal distributions of light (Gaten et al, 1990(Gaten et al, , 1992Johnson et al, 2000aJohnson et al, , 2000bJohnson et al, , 2002. Failure to consider these important factors is likely to lead to anomalous behaviour, physiological damage and erroneous conclusions.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of crustaceans whose spectral sensitivities have been studied (primarily crabs, deep-sea shrimps or stomatopods) are either mono-or di-chromatic (reviewed in Marshall et al, 1999). However, previous research on crustacean spectral sensitivity has found that shallow-water coastal decapods are often dichromatic, with one photoreceptor maximally sensitive to blue-green wavelengths (480-540 nm), and a second UV/blue-sensitive photoreceptor with peak sensitivity near 400 nm (Cronin, 2006;Goldsmith and Fernandez, 1968;Johnson et al, 2002;Marshall et al, 1999Marshall et al, , 2003, although monochromacy among shallow-water decapod crustaceans is not unprecedented (see Marshall et al, 1999 for a review).…”
Section: Discussion Cleaner Shrimp Visual Capabilitiesmentioning
confidence: 99%